Hubungan dimensi kepercayaan (trust) dan dimensi kualitas (quality) dengan partisipasi pelanggan e-commerce :: Studi pada pelanggan e-comeerce di Yogyakarta - AGUSTINA, Duwi ([Yogyakarta] : Universitas Gadjah Mada, 2010)
This research examines relation between trust and quality with e-commerce customer’s participation in Yogyakarta. With regard to this relatively new business exercises especially for Indonesia, there are some interesting phenomena to consider as, for example, how far customers put their trust and quality in ecommerce’s vendors and how their trust has effect on the level of participation in ecommerce. The act of transacting through e-commerce can be said to involve high risk. For that reason, it is obvious that customer trust factor represents primary factor in ecommerce. This research makes use of Indonesia e-commerce users as research samples while using likert scale questionnaire for data collection. Furthermore, the questionnaires are given immediately and sent using e-mail to as many as 133 respondents through mailing list. For data analysis method, this research uses Structural Equation Model or SEM as abbreviated and uses PLS (Partial Least Square) V.20 M3. Out of six predictor variables related to trust and quality (ability, benevolence, and integrity, availability, responsiveness, timeliness), it is only vendor’s integrity and ability that has positive and significant relation with cutomer’s trust, it is only vendor’s availability and responsiveness that has positive and significant relation with cutomer’s quality. And it is only customer’s trust which related to customer’s participation On the other hand, it is only vendor’s integrity, ability, availability responsiveness and customer’s trust that have positive and significant relation with e-commerce customer’s participation in Yogyakarta.